In situ nanobeam electron diffraction strain mapping of planar slip in stainless steel. (15th March 2018) - Pekin, Thomas C.; Gammer, Christoph; Ciston, Jim; Ophus, Colin; Minor, Andrew M.
Abstract: Nanobeam electron diffraction strain mapping has been used to measure the strain evolution in stainless steel under in situ deformation. As the amount of deformation increases, the leading dislocation of a planar slip band leaves behind a residual strain in the form of a small lattice expansion. Dislocation analysis confirmed that the dislocations involved were <011 > type. While the characteristic residual strain of planar slip has often been observed, it has never before been directly measured. Our results provide a view into the dynamic mechanisms of planar slip, and showcase the possibilities of multidimensional in situ imaging. Graphical Abstract: